Respostas
respondido por:
4
a6 = 7
a10 = 15
an = a1 + (n - 1).r
a6 = a1 + (6 - 1).r
a6 = a1 + 5.r
7 = a1 + 5.r ⇒ a1 = 7 - 5.r (1)
a10 = a1 + (10 - 1).r
15 = a1 + 9.r ⇒ a1 = 15 - 9.r (2)
Igualando (1) com (2), temos:
7 - 5.r = 15 - 9.r
9.r - 5.r = 15 - 7
4.r = 8
r = 8/4
r = 2
Resposta: r = 2
Espero ter ajudado.
a10 = 15
an = a1 + (n - 1).r
a6 = a1 + (6 - 1).r
a6 = a1 + 5.r
7 = a1 + 5.r ⇒ a1 = 7 - 5.r (1)
a10 = a1 + (10 - 1).r
15 = a1 + 9.r ⇒ a1 = 15 - 9.r (2)
Igualando (1) com (2), temos:
7 - 5.r = 15 - 9.r
9.r - 5.r = 15 - 7
4.r = 8
r = 8/4
r = 2
Resposta: r = 2
Espero ter ajudado.
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás